Pelatihan Pengelolaan Laboratorium IPA bagi Guru SMP/MTs Kecamatan Windusari - Riva Ismawati; Eli Trisnowati (IKIP PGRI Bojonegoro, 2019)
ABSTRACTLearning science in junior high schools cannot be separated from activities in the laboratory. Professional laboratory managers are an important aspect to support the ongoing science learning process. The results of observations at partner schools found that laboratory managers still had low knowledge about the competence of school laboratory personnel. IPA laboratories in partner schools have not been used according to their functions. In addition, the tools and materials available have not been handled properly so that they are not maintained, and cannot be used optimally. The objectives of this service are: a) participants understand the organizational structure and tasks of laboratory personnel, b) participants can develop, implement, evaluate laboratory work programs; c) participants can apply occupational safety health in the laboratory; d) participants can carry out maintenance and maintenance of tools and materials. Implementation methods include lectures, discussions, practices, and assignments. Evaluation of the service implementation is carried out at the end of the activity to find out the participants' responses to the activities that have been carried out. The result of this service activity is the increasing skills of trainees in managing the science laboratory.Keywords: training, management, science laboratory. ABSTRAKPembelajaran IPA di SMP tidak dapat dipisahkan dari kegiatan di laboratorium. Pengelola laboratorium yang professional merupakan aspek penting sebagai pendukung berlangsungnya proses pembelajaran IPA. Hasil observasi di sekolah mitra diketahui pengelola laboratorium masih memiliki pengetahuan yang rendah mengenai kompetensi tenaga laboratorium sekolah. Laboratorium IPA di sekolah mitra belum digunakan sesuai dengan fungsinya. Selain itu, alat dan bahan yang tersedia belum ditangani dengan baik sehingga tidak terawat, dan tidak dapat difungsikan secara optimal. Tujuan kegiatan pengabdian ini adalah a) peserta memahami struktur organisasi dan tugas tenaga laboratorium, b) peserta dapat menyusun, melaksanakan, mengevaluasi program kerja laboratorium; c) peserta dapat menerapkan kesehatan keselamatan kerja di laboratorium; d) peserta dapat melakukan perawatan serta pemeliharaan alat dan bahan. Metode pelaksanaan meliputi ceramah, diskusi, praktik, dan penugasan. Evaluasi pelaksanaan pengabdian dilakukan diakhir kegiatan untuk mengetahui tanggapan peserta terhadap kegiatan yang telah dilaksanakan. Hasil kegiatan pengabdian ini adalah meningkatnya keterampilan peserta pelatihan dalam mengelola laboratorium IPA. Kata Kunci: pelatihan, pengelolaan, laboratorium IPA.